2020
DOI: 10.1002/marc.201900610
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Sugar‐Sensing Hydrogels

Abstract: The ability of boronic acids (BAs) to reversibly bind diols, such as sugars, has been widely studied in recent years. In solution, through the incorporation of additional fluorophores, the BA–sugar interaction can be monitored by changes in fluorescence. Ultimately, a practical realization of this technology requires a transition from solution‐based methodologies. Herein, the first example of 3D‐printed sugar‐sensing hydrogels, achieved through the incorporation of a BA–fluorophore pair in a gelatin methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Generally, T gel in such a range is fast enough to achieve successful 3D printing. [50,51] Figure 5c further shows that, upon exposing the PTH precursor to the intermittent light irradiation, the increase of G' and G" is only observed when the visible light is on. However, no change is found in these two parameters without visible light irradiation.…”
Section: D Printing Of Pthsmentioning
confidence: 87%
“…Generally, T gel in such a range is fast enough to achieve successful 3D printing. [50,51] Figure 5c further shows that, upon exposing the PTH precursor to the intermittent light irradiation, the increase of G' and G" is only observed when the visible light is on. However, no change is found in these two parameters without visible light irradiation.…”
Section: D Printing Of Pthsmentioning
confidence: 87%
“…Consider, for example, a material that swells and contracts in response to glucose concentration and using this response to control the release of insulin. Such materials are known (Bruen et al, 2020), but even if insulin control using a materials only approach can be demonstrated convincingly, can this be presented in a manner acceptable to society as the next step on the road towards the artificial pancreas which, in the heady excitement of the 1980s, appeared to be on the cusp of happening?…”
Section: The Futurementioning
confidence: 99%
“…Hydrogels represent 3-D hydrophilic, polymeric platforms, which hold potential preserve large quantities of water or biological fluids. Aerogels are extremely porous and provide large internal surfaces with exceptional drug delivery capabilities [190,191]. Almost all of these gels are static and brittle; however, polysaccharides form xerogels and they tend to generate transparent hydrogels, which spontaneously shape interconnected polymers.…”
Section: Drug Retention In Aerogel Layer and Hydrogelsmentioning
confidence: 99%